Adsorption and Photocatalytic Decomposition of the β-Blocker Metoprolol in Aqueous Titanium Dioxide Suspensions: Kinetics, Intermediates, and Degradation Pathways - Violette Romero; Pilar Marco; Jaime Giménez; Santiago Esplugas (International Journal of Photoenergy)
This study reports the photocatalytic degradation of the β-blocker metoprolol (MET) using TiO2 suspended as catalyst. A series of photoexperiments were carried out by a UV lamp, emitting in the 250–400 nm range, providing information about the absorption of radiation in the photoreactor wall. The influence of the radiation wavelength on the MET photooxidation rate was investigated using a filter cutting out wavelengths shorter than 280 nm. Effects of photolysis and adsorption at different initial pH were studied to evaluate noncatalytic degradation for this pharmaceutical. MET adsorption onto titania was fitted to two-parameter Langmuir isotherm. From adsorption results it appears that the photocatalytic degradation can occur mainly on the surface of TiO2. MET removed by photocatalysis was 100% conditions within 300 min, while only 26% was achieved by photolysis at the same time. TiO2 photocatalysis degradation of MET in the first stage of the reaction followed approximately a pseudo-first-order model. The major reaction intermediates were identified by LC/MS analysis such as 3-(propan-2-ylamino)propane-1,2-diol or 3-aminoprop-1-en-2-ol. Based on the identified intermediates, a photocatalytic degradation pathway was proposed, including the cleavage of side chain and the hydroxylation addition to the parent compounds.